Choice of Healthcare Services and Its Influencing Factors in the Sunyani Municipality - Asante, A.G. (University Of Ghana, 2020)
Globally, there are a lot of healthcare services available for people to utilize. However, several factors affect the choice of healthcare leading to the non-usage of the right healthcare services. This study sought to assess the choice of healthcare services and its influencing factors in the Sunyani Municipality of Ghana. Adapting Kroeger’s health behavioural model, the study specifically looked at the types of health care services used by different socio-economic groups; the factors influencing choice of health care services; and the barriers that affect choice of health care services. A mixed-method strategy was employed to distribute questionnaires to 430 respondents in four communities within the Sunyani municipality. Also, interviews and focus group discussions were organized with health professionals and community members, respectively. With the help of the SPSS software version 22, the quantitative data was analysed using tables, graphs and cross tabulations as well as a logistic regression model to predict factors that affect the choice of healthcare services for both adults and children. With the qualitative data the NVivo software was used to generate themes, and relevant quotes used to support the quantitative data. The study revealed that the choice of healthcare does not necessarily vary among different socio-economic groups when it comes to choosing healthcare for both adults and children. Although factors such as age, gender, education, income, type of settlement, travel time and distance influence choice of healthcare, these factors affect choice differently depending on the household members involved (children or adults) and the nature of illness (chronic or acute). The study also revealed that distance to a health facility, nature of transport services, waiting times, attitude of health professionals, inadequate medical equipment, cost of service, none acceptance of NHIS, and religious/cultural beliefs are some of the barriers that impede healthcare choice. It is recommended that there should be an untargeted approach by the Ghana Health Service in public education on the use of the right healthcare and the need to seek formal healthcare in all medical conditions within the Sunyani Municipality. Additionally, government and other stakeholders should make conscious efforts at removing barriers that affect healthcare access and usage in the Sunyani Municipality.
MPhil. Geography and Resource Development
Keywords: Healthcare Services; Sunyani Municipality